(untitled) (Patrimônio e Memória, 2024)
This paper aims to develop some reflections on the figure of work and the worker in João Antônio’s fiction, based on an approach to the short stories published in the author’s debut book, Malagueta, Perus and Bacanaço (1963). It is possible to perceive, in the set of short stories present in the collection, a certain identity between the social experiences represented, which occur beyond the different social origins of the characters in each story. In this way, it may be possible to perceive João Antônio’s original contribution to the representation of the Brazilian working classes, their possible desires and dilemmas, participating in a tradition that, in one way or another, is still present in authors of contemporary generations.